Submission of deduction programme against L/C remaining unadjusted amount - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of of deduction program against LC remaining unadjusted amount for BRACU new campus project.